Safety and efficacy of en bloc transurethral resection versus conventional transurethral resection for primary nonmuscle-invasive bladder cancer: a meta-analysis - Zhang, Dong (World J Surg Oncol, 2020)
BACKGROUND: The purpose of this meta-analysis is to compare the safety and efficacy of en bloc transurethral resection of bladder tumor (EBRT) versus conventional transurethral resection of bladder tumor (CTURBT). METHODS: We performed a meta-analysis of relevant articles through November 2019 using PubMed, Embase, and Cochrane Central Register to compare the safety and efficacy of EBRT versus CTURBT. The main endpoint included the operation time (OT), hospitalization time (HT), catheterization time (AT), perioperative period complications, bladder detrusor muscle found in the specimen, the residual tumor on the base, the ratio of the same site recurrence, and 12/24/36-month recurrence rate. Cochrane Collaboration’s Revman software, version 5.3, was used for statistical analysis. RESULTS: A total of 19 studies with 2651 patients were included, 1369 underwent EBRT and 1282 underwent CTURBT. Patients treated with EBRT had a significantly lower AT, HT, obturator nerve reflex, bladder perforation, bladder irritation, postoperative complications, and 24-month recurrence rate than those who underwent CTURBT. While no significant difference was found in terms of OT, the ratio of bladder detrusor muscle found in the specimen, the residual tumor on the base, 12-month recurrence rate, 36-month recurrence rate, and the ratio of the same site recurrence. In mitomycin subgroup, EBRT was superior to CTURBT in terms of 12/24-month recurrence rate. Similarly, in the prospective subgroup and retrospective subgroup, EBRT had a lower 24-month recurrence rate than CTURBT. However, no significant difference was found in the low, intermediate, and high-risk group in the light of 12–36-month recurrence rate. CONCLUSIONS: Based on the included 19 articles, EBRT had a significantly lower AT, HT, intraoperative and postoperative complications, and 24-month recurrence rate than those treated with CTURBT. Well-designed randomized controlled trials were needed to reevaluate these outcomes. TRIAL REGISTRATION: This meta-analysis was reported in agreement with the PRISMA statement and was registered on PROSPERO 2019 CRD42019121673.